2020
DOI: 10.1098/rsta.2020.0062
|View full text |Cite
|
Sign up to set email alerts
|

The direct synthesis of hydrogen peroxide from H 2 and O 2 using Pd–Ni/TiO 2 catalysts

Abstract: The direct synthesis of hydrogen peroxide (H 2 O 2 ) from molecular H 2 and O 2 offers an attractive, decentralized alternative to production compared to the current means of production, the anthraquinone process. Herein we evaluate the performance of a 0.5%Pd–4.5%Ni/TiO 2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Although in recent years great strides have been made in improving catalyst selectivity through the incorporation of numerous secondary metals into supported Pd catalysts. Perhaps most extensively studied has been the enhancement in catalytic efficacy through the alloying of Pd with Au, [8][9][10][11][12] however numerous investigations have demonstrated that the addition of a range of abundant metals including Fe, 13,14 Sn, 15,16 Ni, 17,18 In, 19 Ag, 20 Zn, 21,22 Te 23 and Co 24 can similarly enhance catalytic performance. Further studies have focussed on the incorporation of dopant levels of precious metals, in particular Pt, into supported Pd, [25][26][27][28] Au 29 and AuPd catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Although in recent years great strides have been made in improving catalyst selectivity through the incorporation of numerous secondary metals into supported Pd catalysts. Perhaps most extensively studied has been the enhancement in catalytic efficacy through the alloying of Pd with Au, [8][9][10][11][12] however numerous investigations have demonstrated that the addition of a range of abundant metals including Fe, 13,14 Sn, 15,16 Ni, 17,18 In, 19 Ag, 20 Zn, 21,22 Te 23 and Co 24 can similarly enhance catalytic performance. Further studies have focussed on the incorporation of dopant levels of precious metals, in particular Pt, into supported Pd, [25][26][27][28] Au 29 and AuPd catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…23 In addition, the activity of monometallic and bimetallic catalysts can be improved by selecting more suitable support materials such as TiO 2 , carbon-based substrates, zeolites, γ-Al 2 O 3 , hydroxyapatite (HAp), mesoporous alumina, amorphous silica-alumina, etc. [24][25][26][27][28] For example, Wang et al have employed a porous hypercrosslinked ionic polymer as an efficient support for the immobilization of Pd nanoparticles and employed this catalyst in the heterogeneous aerobic oxidative coupling of diaryl ethers. 29 In the present study, boron nitride nanosheets because of their excellent properties such as high surface area, high mechanical strength, and chemical and thermal stability, were an excellent choice as the support for uniform stabilization of Pd-Au nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…8,11,12 However, due to limited selectivity there is often a need to alloy Pd with a range of precious metals, [13][14][15][16][17] although in recent years, a growing attention has been placed on the use of more abundant transition metals as promoters for Pd. [18][19][20][21][22][23] Indeed, we have recently demonstrated the ability of bi-functional Pdbased bimetallic nanoparticles to catalyse the direct synthesis of H 2 O 2 in addition to the selective oxidation of a range of substrates [24][25][26] as well as the remediation of microorganisms through radical pathways. 27 With these studies in mind, we now investigate the efficacy of supported Pd-based bimetallic catalysts that combine the H 2 O 2 synthesising activity of Pd and the ability of a range of transition metals to generate reactive oxygen species through Fenton's pathways for the degradation of phenol.…”
Section: Introductionmentioning
confidence: 99%